A comparative study on the impact of service quality on customer satisfaction: Survey of joint venture and government banks in Nepal - Ghimire, Shiva Raj; Agarwal, Nirdosh; Basnet, Ashok; Chaurasiya, Sneha (Journal of Commerce, Management, and Tourism Studies, 2024)
This study explores the relationship between customer satisfaction and service quality, of the inquiry is the evaluation of client satisfaction regarding the caliber of service rendered by Nepalese commercial banks. The study attempts to determine the effect of focusing on how important it is for service quality to influence customer contentment. The primary focus service quality on customer satisfaction within the Nepalese banking industry is by using descriptive and causal comparative research techniques. A total of 383 samples were taken from six joint venture banks and three public (or Government ownership) banks in Nepal. Using primary data obtained from a survey with a five-point Likert scale, correlation and regression analysis are used in the study to examine the impact of several service quality parameters on customer satisfaction. The results show that, in the Nepalese banking industry, responsiveness, reliability, assurance, and empathy have a positive and significant association with customer satisfaction. However, responsiveness does not significantly affect customer satisfaction.